Insect biodiversity for sustainable management of natural resources - Goergen, Georg E. (2010)
This paper discusses the conservation of biodiversity and the sustainable use of natural resources in the African continent and the role of insect biodiversity for the sustainable development of natural resources. The arthropod reference collection at the Agricultural Research for Development in Africa (IITA) in Bénin that currently encompasses more than 350 000 specimens collected in a wide range of agricultural and natural environments throughout West Africa is also highlighted.